What Can a Hypnotic Induction Do?. Issue 2 (14th October 2016) - Woody, Erik; Sadler, Pamela
Abstract : In contrast to how recent definitions of hypnosis describe the induction, a work-sample perspective is advocated that characterizes the induction as an initial, stage-setting phase encompassing everything in a hypnotic session up to the first hypnotic suggestion of particular relevance to the therapeutic or research goals at hand. Four major ways are then discussed in which the induction could affect subsequent hypnotic responses: It may provide information about how subsequent behaviors are to be enacted; it may provide cues about the nature of the interpersonal interaction to be expected in hypnosis; it may provide meta-suggestions, defined as suggestive statements intended to enhance responses to subsequent hypnotic suggestions; and it may provide a clear transition to help allow new behaviors and experiences to emerge. Several ideas for future research are advanced, such as mapping hypnosis style onto the interpersonal circumplex, evaluating whether attentional-state changes measured at the end of the induction actually mediate subsequent hypnotic responsiveness, and systematically examining the impact of ritual-like aspects of inductions.